Afgan Immigrants' cultural Adaptation in Khaled Hossaeini's Kite Runnner - SONI PRASETYO ARIFIN (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
This study deals with Afgan Immigrants' cultural adaptation in Khaled Hossaeini's Kite Runner. This writing of this study is based on the knowledge of cross cultural understanding which tells about immigrant's cultural adaptation in the new country. The term of cultural adaptation is proposed by Prof. Tyalor Burnett while the cultural adaptation process is based on Anthony. The impacts of cultural adaptation will be depicted by cultural identity by Pratt Nicola as the main revelation of the impacts of cultural adaptation process. Then,the from the several impacts which happened like Diaspora by William Safren,Double consciousness which causes unhomeliness, by Du Bois, the mimicry which causes imitation also hybridity which causes hybrid culture by Hommi Bhaba. The purpose of the study is to describe the cultural adaptation process and to reveal the impacts of cultural adaptation which is happened in the novel. Data are collected ,classified and analyzed to explain the cultural adaptation process and impacts of cultural adaptation .The analysis is conducted by applying rhetorical framework in the statement of problems. The analysis shows that cultural adaptation process describes the four stage of cultural adaptation process which happened in novel. Then the impacts of cultural adaptation process are revealed four impacts. Those are Diaspora,Unhomeliness , imitation, and hybrid culture.Those impacts can be happened in each Afgan immigrant who tries to adapt in new place which has different culture.Those impacts can be different depends on their cultural adaptation process in each stage. Keywords: Culture,Cultural Adaptation Process, Cultural Identity